PENTINGNYA MENJAGA KESEHATAN UMUM DAN REPRODUKSI WANITA SEMASA HIDUP - Wratsangka, Raditya; Murthi, Aditya Krishna; Tungka, Endrico Xavierees; Tjhin, Purnamawati; Venantius, Alvin (Jurnal Pengabdian Masyarakat Trimedika, 2025)
The life course approach emphasizes the importance of maintaining health form adolescence to elderly, including sexual and reproductive health, non-communicable diseases, and mental health. Promotive and preventive efforts in the form of health education are still needed as one of the most realistic steps to help optimize women's health status. This community service activity was carried out on November3, 2024 to 68 Catholic women from various age groups who are members of the Indonesian Catholic Women's Association. The activities carried out were in the form of health education with the topic " Becoming a Healthy woman form Age to Age" and collecting questionnaire data. The results showed that after participating in this activity, the level of awareness improved regarding the importance of implementing a healthy lifestyle and routine health checks as a promotive and preventive effort to prevent disease in adult to elderly women. The conclusion of this activity is that health education needs to be carried out continuously to avoid misinformation in effort's to maintain women's health so that women's health status can reach optimal levels in various age groups.